The world according to Garp [compact disc, unabridged] - Irving, John, 1942- (Random House AudioBooks, 1998)
A worldwide bestseller since its publication, Irving's classic is filled with stories inside stories about the life and times of T. S. Garp, struggling writer and illegitimate son of Jenny Fields - an unlikely feminist heroine ahead of her time. Beautifully written, THE WORLD ACCORDING TO GARP is a powerfully compelling and compassionate coming-of-age novel that established John Irving as one of the most imaginative writers of his generation.